(untitled) (Global Journal of Human-Social Science, 2024)
This article deals with values component inherent for advertising discourse. Values in advertising discourse influence the recipients and achieve their pragmatic goals. Advertising discourse mirrors the values that have already existed in a particular society. It also forms new values and implements them into people’s minds creating new forms of reality where the possession of a good is more desirable than that of the real needs of a consumer. Values representation in the advertising discourse highlights the most significant cultural meanings of the dominant values, which are widely represented by the explication of hedonistic, social, and material values determined by the necessary requests of the recipients.